2016
DOI: 10.1103/physrevlett.116.117601
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Photoluminescence Response by Electric Field in Electrically Soft Ferroelectrics

Abstract: We show that an electrically soft ferroelectric host can be used to tune the photoluminescence (PL) response of rare-earth emitter ions by external electric field. Photoluminescence (PL) property of lanthanide ions is a subject of continuing interest because of its enormous applications in lighting industry, Laser, fiber optics telecommunications, biological assaying and medical imaging [1,2]. The most common strategy prevalent among experimentalists is to investigate the PL response/mechanisms by placing the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(39 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…To get deeper insight into the local crystal ordering or distortions (symmetries) inside the NbO 6 octahedrons, the photoluminescence behavior of Eu 3+ ion is employed to observe their behaviors. As well‐known, the photoluminescence performance of Eu 3+ ion is very sensitive to the phase transition or even small distortion in the crystal structure . From the radius perspective, Eu 3+ ion is expected to occupy the sites of K + and Na + because the radius of Eu 3+ ion is close to those of K + and Na + ions in the KNN– x LN ceramics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To get deeper insight into the local crystal ordering or distortions (symmetries) inside the NbO 6 octahedrons, the photoluminescence behavior of Eu 3+ ion is employed to observe their behaviors. As well‐known, the photoluminescence performance of Eu 3+ ion is very sensitive to the phase transition or even small distortion in the crystal structure . From the radius perspective, Eu 3+ ion is expected to occupy the sites of K + and Na + because the radius of Eu 3+ ion is close to those of K + and Na + ions in the KNN– x LN ceramics.…”
Section: Resultsmentioning
confidence: 99%
“…As Rubio‐Marcos et al reported, it is useful to study the relationship between the structures and the piezoelectric properties of KNN‐based ceramics using the Raman spectroscopy. On the other hand, it has been reported that the photoluminescence spectroscopy of trivalent europium ion (Eu 3+ ) can be used as a probe for small structural distortions caused by phase transition, which have been observed in both glasses and ceramics . Thus, a promising method, by investigating the photoluminescence emission of Eu 3+ ion, is proposed to analyze the deformation of the NbO 6 octahedral distortion caused by the spontaneous electric dipole.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the complexity (coexistence of phases) and interference arisen from the strong diffraction peaks of ITO, the Rietveld refinement method has not been used for precisely identifying the crystal structure. Instead, with the primary aim of verifying the change of crystal structure, the broad diffraction peak has been resolved by the practical peak fitting method25, giving the fitting results indicated in Fig. 2b.…”
Section: Resultsmentioning
confidence: 99%
“…The uneven components enhance the electronic coupling between 4f energy levels and higher 4f5d configuration and subsequently increase f–f transition probabilities of the dopant ions19. The common approaches for ferroelectric hosts to rationally tune structural symmetry are based on those coupling physical factors that can respond well to external electric field such as biaxial strain1420, polarization2212223, or phase transition2425.…”
mentioning
confidence: 99%